Failure of adhesive bonds between proteoglycans causes viscoelasticity of soft tissues. Issue 1 (October 2016) - Hillgärtner, Markus; Linka, Kevin; Itskov, Mikhail
Abstract: Soft tissues can be considered as a composite material where a matrix (ground substance) is reinforced by collagen fibers. These fibers consist of fibrils, which are connected by proteoglycan (PG) bridges. The time‐dependent properties of soft tissues appear to be mainly caused by proteoglycans [3]. This contribution presents a modeling approach where damage in the PG bridges arises due to the failure of the covalent bonds between two proteoglycans. The breakage of covalent bonds is reversible over time and incorporated using a healing formulation. A high PG density supports interfibrillar sliding and hence leads to a lower fibril stretch [8]. Accordingly, the damage propagation in PG bridges leads to a higher stretch in the fibrils and therefore to a stiffer material response. The strain energy of the fibrils is based on the response of single tropocollagen molecules and takes both, an entropic and an energetic regime into account [5]. Finally, the model is compared against experimental data available in the literature. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)